2006
DOI: 10.1038/sj.npp.1301100
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Genes in Monoamine Nuclei that may Determine Stress Vulnerability and Depressive Behavior in Wistar–Kyoto Rats

Abstract: The Wistar-Kyoto (WKY) rat is stress sensitive and exhibits depressive-like behavior. The locus coeruleus (LC)-norepinephrine and dorsal raphe (DR)-serotonin systems mediate certain aspects of the stress response and have been implicated in depression. Microarray technology was used to identify gene expression differences in the LC and DR between WKY vs Sprague-Dawley (SD) rats that might account for the WKY phenotype. RNA was isolated from microdissected LC and DR, amplified, and hybridized to microarrays (1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 74 publications
4
43
0
Order By: Relevance
“…In this regard, previous studies have implicated the dynorphin--OR system in depression and suggest that -OR antagonists may be useful antidepressants (Pliakas et al, 2001;Mague et al, 2003;McLaughlin et al, 2003McLaughlin et al, , 2006bShirayama et al, 2004). Although these studies focused on -OR actions in forebrain, findings of increased -OR gene expression in the LC of the Wistar-Kyoto rat (a strain that exhibits a depressive phenotype) support a role for -OR in the LC in depression (Pearson et al, 2006). In other clinical conditions that are characterized by excessive responses to sensory stimuli, the ability of -OR agonists to blunt these responses without altering the state of arousal might be therapeutically useful.…”
Section: Presynaptic Actions Of Opiate Receptors In Brainmentioning
confidence: 77%
See 1 more Smart Citation
“…In this regard, previous studies have implicated the dynorphin--OR system in depression and suggest that -OR antagonists may be useful antidepressants (Pliakas et al, 2001;Mague et al, 2003;McLaughlin et al, 2003McLaughlin et al, , 2006bShirayama et al, 2004). Although these studies focused on -OR actions in forebrain, findings of increased -OR gene expression in the LC of the Wistar-Kyoto rat (a strain that exhibits a depressive phenotype) support a role for -OR in the LC in depression (Pearson et al, 2006). In other clinical conditions that are characterized by excessive responses to sensory stimuli, the ability of -OR agonists to blunt these responses without altering the state of arousal might be therapeutically useful.…”
Section: Presynaptic Actions Of Opiate Receptors In Brainmentioning
confidence: 77%
“…This is of particular interest as dynorphin and -ORs are implicated in stress-related disorders (Pliakas et al, 2001;Mague et al, 2003;McLaughlin et al, 2006a). Moreover, elevated -OR gene expression in the LC of Wistar-Kyoto (WKY) rats, a strain that has been used to model stress-related depression, suggests that -OR activation in this nucleus may have clinically relevant consequences (Pearson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression studies with the help of microarray technology identified the differential gene expression between WKY rats and SD rats in the locus coeruleus (LC) and dorsal raphe (DR) which are key sites of origin for noradrenergic and serotonergic pathways, respectively (Pearson et al, 2006). Differences in gene expression in LC or DR neurons could underlie differential responses of these systems to stress and account for the stress-sensitive phenotype of the WKY strain.…”
Section: Wky Rat Model -Genetic Model Of Hyperalgesia Associated Withmentioning
confidence: 99%
“…Along with the genetic impairment of noradrenergic systems, an increased expression of genes encoding opioids, and orexin (hypocretin) which regulates the neurotransmitters that convey afferent information to the LC was reported. The low expression of genes encoding cytoskeletal proteins that are important for structural plasticity and several potassium channels, suggests that the excitability and synaptic integration of DR neurons may be altered in WKY rats (Pearson et al, 2006).…”
Section: Wky Rat Model -Genetic Model Of Hyperalgesia Associated Withmentioning
confidence: 99%
“…Several QTL (Imm 1 D2Rat188, Imm3 D5Rat40, Imm6 D16Arb5, Climb2 D1Rat147, FST1 D16Rat75) were identified for climbing, immobility and swimming in WKY rats, sharing common target regions with susceptibility loci mapped by genome scan analyses for emotionality QTL in rodents and human genetic linkage to emotional disorder (Solberg et al, 2004). Significance of microarray analysis (SAM) revealed that expression of 66 genes was increased in the locus coeruleus (LC) of WKY compared to SD rats (Pearson et al, 2006), including genes that encoded for enzymes involved in NE turnover. Moreover, the mRNA of catechol-O-methyltransferase (COMT), a key enzyme in the catabolism of catecholamines, was found at levels four-to sevenfold higher in the cerebral cortex in WKYs than SDs (Walker et al, 2004).…”
Section: Genetic Componentsmentioning
confidence: 99%